Stability of exercise addiction symptoms and co-occurring mental disorders – a follow-up study - Meyer, Maximilian; Wagner, Aline; Schmidt, André; Schaub, Anna-Chiara; Lang, Undine E.; Walter, Marc; Colledge, Flora (Frontiers in Psychiatry, 2025)
IntroductionIndividuals with exercise addiction (EA) report being unable to stop exercising despite its negative psychological, physical, or social impact. Due to a lack of evidence, EA has so far not been officially recognized as a behavioral addiction. Only one study exists, that investigated mental disorders in individuals with EA by utilizing the Structured Clinical Interview for DSM-5 Disorders (SCID-5). The present study followed up on this sample, providing the first longitudinal data on EA.MethodsAll participants of the baseline study were invited to complete validated psychometric instruments assessing symptoms of depression, attention deficit hyperactivity disorder, trauma, and EA. Furthermore, an exhaustive diagnostic assessment with the SCID-5-CV, the SCID-5-PD (following a SAPAS screening), and a self-designed clinical interview to assess EA criteria were conducted.ResultsThe response rate was 59.4% (n=19) and the mean duration of follow-up was 634.5 (SD=155.8) days. Number of fulfilled EA criteria in the sample remained largely stable over time with no change in seven (36.8%), a reduction in nine (47.4%), and an increase in three (15.8%). Eighteen out of 19 participants fulfilled the criteria for at least one mental disorder. The most prevalent disorders were major depressive disorder (lifetime prevalence 73.7%; n=14) and obsessive-compulsive personality disorder (52.6%; n=10).DiscussionThis data suggests that EA is a temporary stable and distinct disorder with affected individuals suffering from severe psychological distress. Further studies are necessary to investigate potential cause-effect relationships between co-occurring mental disorders and EA.